2016
DOI: 10.1038/srep19823
|View full text |Cite
|
Sign up to set email alerts
|

Characters related to higher starch accumulation in cassava storage roots

Abstract: Cassava (Manihot esculenta) is valued mainly for high content starch in its roots. Our understanding of mechanisms promoting high starch accumulation in the roots is, however, still very limited. Two field-grown cassava cultivars, Huanan 124(H124) with low root starch and Fuxuan 01(F01) with high root starch, were characterised comparatively at four main growth stages. Changes in key sugars in the leaves, stems and roots seemed not to be strongly associated with the final amount of starch accumulated in the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 53 publications
1
34
0
2
Order By: Relevance
“…The assay was performed in the reverse direction using phosphoglucomutase and Glucose-6-phosphate dehydrogenase to couple Glucose-1- phosphate formation in real time to NADP + reduction and then measured by spectrophotometers. The crude extracts were obtained as described by Li et al (2016b), adapted to cassava leaves. Briefly, 0.1 g of fresh tissue fully homogenized on ice in a 0.3 ml pre-cooled solution composed of 100 mM Hepes-NaOH at pH 7.4, 8 mM MgCl 2 , 2 mM EDTA, 12.5% (v/v) glycerol, 5% (v/v) polyvinylpyrrolidone, and 50 mM β - mercaptoethanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay was performed in the reverse direction using phosphoglucomutase and Glucose-6-phosphate dehydrogenase to couple Glucose-1- phosphate formation in real time to NADP + reduction and then measured by spectrophotometers. The crude extracts were obtained as described by Li et al (2016b), adapted to cassava leaves. Briefly, 0.1 g of fresh tissue fully homogenized on ice in a 0.3 ml pre-cooled solution composed of 100 mM Hepes-NaOH at pH 7.4, 8 mM MgCl 2 , 2 mM EDTA, 12.5% (v/v) glycerol, 5% (v/v) polyvinylpyrrolidone, and 50 mM β - mercaptoethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 0.1 g of fresh tissue fully homogenized on ice in a 0.3 ml pre-cooled solution composed of 100 mM Hepes-NaOH at pH 7.4, 8 mM MgCl 2 , 2 mM EDTA, 12.5% (v/v) glycerol, 5% (v/v) polyvinylpyrrolidone, and 50 mM β - mercaptoethanol. Then, a 20 μL aliquot of the crude enzyme extract was used to start the assay as detail Li et al (2016b). Absorbance values at 340 nm of the reaction solution were normalized by absorbance values at 340 nm resulting from the control.…”
Section: Methodsmentioning
confidence: 99%
“…The authors also showed that a higher starch accumulation in tuberous root is related to a higher phloem transport due to an up‐regulation of the expression of sugar transporter genes in stem. Moreover, this study showed that a more compact arrangement of the xylem bundles combined with a limited amount of callose in sieve tubes resulted to more dynamic fluxes and higher sugar export towards tuberous root, thereby yielding cultivars with higher starch content (Li et al ).…”
Section: Fate Of Sugar Inside and Outside The Rootmentioning
confidence: 99%
“…This study also indicated an important role of three 14‐3‐3 proteins isoforms (enzymes involved in the regulation of primary metabolism and cellular processes by protein–protein interactions) in this process (Wang et al ). Finally, a comparative study of two cassava cultivars, one with low (Huanan 124, H124), another with high (Fuxuan 01, F01) root starch content indicated that difference in starch accumulation in both cultivars was not linked with soluble sugar amounts in leaves, stem and roots, but rather with a higher starch synthesis activity and a lower amylase activity in roots (Li et al ). The authors also showed that a higher starch accumulation in tuberous root is related to a higher phloem transport due to an up‐regulation of the expression of sugar transporter genes in stem.…”
Section: Fate Of Sugar Inside and Outside The Rootmentioning
confidence: 99%
“…There was significantly higher expression of genes for several key rate-limiting enzymes in the glycolysis pathway (PFK, PGK and PK, GAPDH and ALDO) in stems of domesticated cassava compared with W14, as well as 212 members transcription factor families. According to information from biochemical and transcriptome analysis of stem phloem sap, there is a powerful stem transport capacity which may affect starch accumulation in the storage roots [35] . Cassava stems are used for reproduction and to keep the plant upright, whereas the roots store materials, which differs from most plants where bulbs or tubers are used for material storage and reproduction [21] .…”
Section: Expression Of Active Sucrose Degradation and Transport Genesmentioning
confidence: 99%